A better zoning system for South Africa?. (September 2016) - Nel, Verna
Highlights: South Africa requires land use management that promotes redress, social justice, spatial resilience and sustainability. New legislation requires land use zoning but this has been criticised for being exclusionary, unjust and unsustainable. Alternative land use management and control systems are evaluated. An more suitable system based on an adapted transect using appropriate land use management tools is proposed. Abstract: After many years of disjointed legislation, the new Spatial Planning and Land Use Management Act has finally been implemented in South Africa. This legislation requires a holistic spatial planning system that includes development principles, policy, spatial planning on all levels of government, land use management and control. The development principles relate to spatial justice, redress, inclusion, resilience, efficiency, sustainability and good administration. At the same time the act mandates land use zoning as the form of development control, yet zoning has been criticised as being exclusionary, unjust and unsustainable. It is thus in conflict with the principles of the act. This raises the question: if not zoning, what other form of land use management and control will be suitable for South Africa and other countries with a similar colonial history? This paper considers the role of land use management and the criteria for an appropriate system in circumstances of weak municipal government capacity. As part of the argument it considers the arguments around zoning and then evaluates the applicability of alternative forms of development control in the South African context. The paper concludes with a suggestion for a land use management system based on a transect adapted to the South African landscape using various forms of land use management such as performance zoning, form based codes and local spatial plans, where applicable in the local context, within the transect.